1994
DOI: 10.1093/oxfordjournals.jbchem.a124346
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Properties, with Blood Proteins, and Tissue Distribution of 22-Oxa-1α, 25-Dihydroxyvitamin D3, a Noncalcemic Analogue of 1α, 25-Dihydroxyvitamin D3, in Rats1

Abstract: The binding properties, with blood proteins, and tissue distribution of 22-oxa-1 alpha,25-dihydroxyvitamin (22-oxacalcitriol; OCT), a noncalcemic analogue of 1 alpha,25-dihydroxyvitamin D3 [1,25(OH)2D3], in rats were investigated. The binding affinity of OCT to plasma vitamin D binding protein (DBP) is extremely low and OCT mainly circulates in the blood as an intact form nonspecifically bound to lipoproteins especially to chylomicrons and low density lipoprotein (LDL). OCT intravenously injected into normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Here we were able to augment the preliminary identification afforded by HPLC co-chromatography with GC-MS analysis and later comparison with chemically synthesized standards. Furthermore, our work is also consistent with the preliminary finding of a glucuronide conjugate of the 20-hydroxy compound in rat bile following OCT administration (10). The 24R-OH-OCT and 26-OH-OCT in the 25R-form identified here are novel, and their stereochemistry is also established.…”
Section: -Oxacalcitriol Metabolismsupporting
confidence: 90%
See 4 more Smart Citations
“…Here we were able to augment the preliminary identification afforded by HPLC co-chromatography with GC-MS analysis and later comparison with chemically synthesized standards. Furthermore, our work is also consistent with the preliminary finding of a glucuronide conjugate of the 20-hydroxy compound in rat bile following OCT administration (10). The 24R-OH-OCT and 26-OH-OCT in the 25R-form identified here are novel, and their stereochemistry is also established.…”
Section: -Oxacalcitriol Metabolismsupporting
confidence: 90%
“…Lastly, our finding of truncated versions of OCT would seem to open the door to study the origin of the conjugates found in bile in vivo following OCT administration to rats (10). The free 20-oxo or 20-hydroxy compounds identified here would likely be transported to the liver prior to conjugation to glucuronic acid in the hepatocyte, but this remains to be proven.…”
Section: -Oxacalcitriol Metabolismmentioning
confidence: 79%
See 3 more Smart Citations